Conference on Lasers and Electro-Optics 2020
DOI: 10.1364/cleo_at.2020.jth2a.27
|View full text |Cite
|
Sign up to set email alerts
|

Toward Generation of Spatially-Entangled Photon Pairs in a Few-Mode Fiber

Abstract: We describe a novel scheme for spatial-mode-entangled photon-pair generation in a few-mode fiber. We experimentally verify the underlying inter-modal parametric processes with two-mode classical signal input and demonstrate high mode purity of the generated idler.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Similar spatially-entangled photon pairs can also be generated directly in the FMF [26], but, in contrast to PPLN, this requires a different set of two IM-FWM processes, as we have shown for both (LP01, LP11a) [27,28] and orbital-angularmomentum-compatible (LP11a, LP11b) [29] two-mode signal spaces. Using classical-level input signals, we have observed high signal-idler mode selectivity for these two individual processes, and demonstrated that, when combined, these two processes couple the input two-mode seed signal to an orthogonal two-mode idler for various signal-mode superpositions [28,30].…”
Section: Progress On Spatially-entangled Photon-pair Generation In Gu...mentioning
confidence: 83%
“…Similar spatially-entangled photon pairs can also be generated directly in the FMF [26], but, in contrast to PPLN, this requires a different set of two IM-FWM processes, as we have shown for both (LP01, LP11a) [27,28] and orbital-angularmomentum-compatible (LP11a, LP11b) [29] two-mode signal spaces. Using classical-level input signals, we have observed high signal-idler mode selectivity for these two individual processes, and demonstrated that, when combined, these two processes couple the input two-mode seed signal to an orthogonal two-mode idler for various signal-mode superpositions [28,30].…”
Section: Progress On Spatially-entangled Photon-pair Generation In Gu...mentioning
confidence: 83%
“…Gener-ating photon pairs in a superposition of multiple fibers modes requires precise analysis of the phase matching conditions that will allow multiple SFWM processes in the same spectral channel [26,27,28,29]. Experimentally, such phase matching conditions were recently studied for parametric amplification of weak signals [30], but not in the spontaneous regime. Hence correlations between pairs of photons generated in multiple fiber modes were not measured to date.…”
mentioning
confidence: 99%